The Noun Phrases Used İn Nacati Bey's Divan: Necâti Bey’in Divanında İsim Tamlamalarının İncelenmesi (Journal of the College of Languages (JCL), 2020)
The aim of this study is to examine the noun phrases used in Nacati Bey's divan. In this study, we have discussed all kinds of phrases including Arabic and Persian compositions. Because at that time the use of Arabic and Persian compounds was very common. In the introduction, I briefly discussed some of Necati's life. I have benefited from valuable resources. Among these, Zeynep Korkmaz, Muharrem Ergin, Fuat Bozkurt and others. In this study, I have dealt with the subject and type of noun phrases in detail and one by one. In this divan, Persian and Arabic noun phrases are also included. We have been mentioned and explained in this study.